2017
DOI: 10.3389/fneur.2017.00184
|View full text |Cite
|
Sign up to set email alerts
|

Resistant Hypertension after Hypertensive Intracerebral Hemorrhage Is Associated with More Medical Interventions and Longer Hospital Stays without Affecting Outcome

Abstract: BackgroundHypertension (HTN) is the most common cause of spontaneous intracerebral hemorrhage (ICH). The aim of this study is to investigate the role of resistant HTN in patients with ICH.Methods and resultsWe conducted a retrospective study of all consecutive ICH admissions at our medical center from November 2013 to October 2015. The clinical features of patients with resistant HTN (requiring four or more antihypertensive agents to keep systolic blood pressure <140 mm Hg) were compared with those with respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…During an internal resource utilization analysis at our medical center, IV nicardipine was identified as one of the costliest drugs used in the neurological ICU. In addition, our previous study showed that resistant hypertension in patients with ICH is associated with more medical interventions and longer LOS [10]. We therefore hypothesized that early initiation of oral antihypertensives may reduce the use of intravenous nicardipine infusion, ICU LOS, and cost of hospitalization.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…During an internal resource utilization analysis at our medical center, IV nicardipine was identified as one of the costliest drugs used in the neurological ICU. In addition, our previous study showed that resistant hypertension in patients with ICH is associated with more medical interventions and longer LOS [10]. We therefore hypothesized that early initiation of oral antihypertensives may reduce the use of intravenous nicardipine infusion, ICU LOS, and cost of hospitalization.…”
Section: Introductionmentioning
confidence: 97%
“…Spontaneous intracerebral hemorrhage (ICH) is one of the most devastating types of stroke, with an incidence of about 10 per 100,000 person-years in the USA and a Hypertension is the most common risk factor for spontaneous ICH [6,7]. Uncontrolled hypertension is an independent predictor of hematoma expansion, brain edema, neurological deterioration, longer length of stay (LOS) in the intensive care unit (ICU) and hospital, and cost of hospitalization [8][9][10][11]. Intravenous (IV) nicardipine infusion has been shown to be safe and effective for rapid lowering of systolic blood pressure (SBP) to less than 140 mmHg [9,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The real question becomes whether patients with worse admission neurological status also had more refractory hypertension and hence higher nicardipine requirement, and higher hospitalization costs, which could occur irrespective of the timing of oral agent initiation. The authors did address this query in an earlier study of 48 ICH patients with resistant hypertension, requiring ≥ 4 blood pressure agents to maintain SBP ≤ 140 mmHg [10]. In this paper, there was no significant association of resistant hypertension with admission Glasgow Coma Score or ICH score.…”
mentioning
confidence: 68%
“…However, the magnitude of cost and LOS reduction is likely overestimated since the control group was significantly sicker than the intervention group and already prone to longer LOS and higher cost of hospitalization. Third, though the authors had originally intended to test the impact of a protocol they initiated in 2015 which mandated initiation of either amlodipine, lisinopril or both based on admission SBP [10], delays in dysphagia screening among over 12% of the patient population led them to include patients who received a heterogeneous potpourri of oral antihypertensives that were prescribed at the discretion of the treating physician. This heterogeneity injects a level of uncertainty in regards to the impact of drug choice upon outcome.…”
mentioning
confidence: 99%